SIMULTANEOUS ESTIMATION OF SPARFLOXACIN AND DEXAMETHASONE IN BULK AND IN THEIR COMBINED DOSAGE FORM BY HPLC METHOD - Desai, Kirangi B.; Patel, Mayur A; Pradhan, Prasanna K.; Dey, Sudhasatya; Upadhyay, Dr. Umesh M (Asian Journal of Pharmaceutical Research and Development, 2013)
A sensitive, accurate and precise method was developed and validate for the estimation of SPARFLOXACIN and DEXAMETHASONE in bulk and in combined dosage form.The RP-HPLC method had shown adequate separation for Sparfloxacin and Dexamethasone from its degradation products. The separation was achieved on using a C18 column (250 х 4.6 mmi.d.) gradient mixture of phosphate buffer pH 6 and acetonitrile(70:30%v/v) at a flow rate of 1 ml/min, Injection volume 20 µl with detection wavelength of 245 nm. The retention time for Sparfloxacin and Dexamethasone were 3.493±0.5min and 5.049±0.5min respectively. The described method was linear over a range of 30-90 µg/ml for Sparfloxacin and 10-30 µg/ml for Dexamethasone respectively. The correlation coefficient for Sparfloxacin and Dexamethasone were 0.9998 and 0.9997 respectively. The limit of detection for Sparfloxacin and Dexamethasone were 0.005 µg/ml and 0.03µg/ml respectively. The limit of quantification for Sparfloxacin and Dexamethasone were 0.17µg/ml, 0.36 µg/ml respectively. Proposed method was validated as per ICH guidelines for linearity, accuracy, precision, specificity and LOD and LOQ for estimation Sparfloxacin and Dexamethasone in Ophthalmic dosage form and results were found to be satisfactory. Thus the developed and validated stability indicating method can be used successfully for marketed formulations.